Plan de negocios para la creación de una tienda de ropa de bebé, de Acosta Suárez María - Acosta Suárez, María Lizeth (2022)
The objective of this study was to create a physical and online store for the sale of baby clothes in the city of Latacunga. The work focused on the market's analysis to identify the level of consumption, consumption preferences, unsatisfied demand in the area, the application of a questionnaire to the residents of the Salto sector, a nearby place where the physical store will be installed. Subsequently, the preparation of a financial study detailing the investment, costs, and feasibility of the project was appealed. The results obtained in this project show that it is feasible. In addition, generating profitability according to the cost-benefit and having a margin of return within what was planned; this would be within four years after starting the project. In conclusion, the project showed its feasibility, in addition to the presence of an added value, given that the store has online sales and home deliveries, due to the Covid 19 pandemic.